(untitled) (Human Factors in Design, 2023)
People with visual impairments need to use assistive technologies to access Comics (Comic books), such as braille writing and high relief drawing. In this regard, this study aims to apply design to the development of a tactile comic book for visually impaired individuals. Utilizing the design methodology, with a focus on the three macro- areas and rapid manufacturing, such as 3D printing and laser cutting. A prototype of a tactile comic book was developed at the end of this study, using assistive technology and rapid manufacturing for the inclusion of visually impaired individuals.